Transcriptome Sequencing Reveals the Antiviral Innate Immunity by IFN-γ in Chinese Sturgeon Macrophages - Ding, Guangyi; Zheng, Chuwen; Wang, Bei; Zhang, Lifeng; Deng, Dan; Li, Qian; Guo, Huizhi; Zhang, Shuhuan; Xu, Qiaoqing (Frontiers in Immunology, 2022)
To further study the biological function of interferon gamma (IFN-γ) in the Chinese sturgeon (Acipenser sinensis), we conducted transcriptome analysis of primary macrophages induced by IFN-γ using Illumina sequencing technology. We obtained 88879 unigenes, with a total length of 93919393 bp, and an average length of 1057bp. We identified 8490 differentially expressed genes (DEGs) between the untreated and IFN-γ-treated macrophages, with 4599 being upregulated and 3891 downregulated. Gene ontology (GO) analysis showed that 4044 DEGs were enriched in the biological process, cellular component, and molecular function categories. Kyoto Encyclopedia of Genes and Genomes (KEGG) identified 278 immunity-related pathways that were enriched for the DEGs. According to the GO enrichment results, eight key immunity-related genes were screened for verification using qPCR. Results indicate that IFN-γ can activate macrophage Interferon Regulatory Factors (IRFs) and type I interferon (IFN-I), activate RIG-I-like and Toll-like receptor related pathways, and improve the antiviral ability of macrophages in Chinese sturgeon.